2021
DOI: 10.1093/cercor/bhab057
|View full text |Cite
|
Sign up to set email alerts
|

Linked Social–Communication Dimensions and Connectivity in Functional Brain Networks in Autism Spectrum Disorder

Abstract: Much recent attention has been directed toward elucidating the structure of social interaction–communication dimensions and whether and how these symptom dimensions coalesce with each other in individuals with autism spectrum disorder (ASD). However, the underlying neurobiological basis of these symptom dimensions is unknown, especially the association of social interaction and communication dimensions with brain networks. Here, we proposed a method of whole-brain network-based regression to identify the funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 55 publications
2
6
0
Order By: Relevance
“…Crucially, we find the network model generalizes out of sample, increasing confidence in the model. In line with other dimensional work in neurodiverse populations (Lake et al 2019; Rohr et al 2020; Xiao et al 2021), we observe the brain correlates identified by the model are complex and distributed across broad swaths of cortical, subcortical, and cerebellar regions. Using connectome-based identification (ID) (Finn et al 2015; Kaufmann et al 2017; Vanderwal et al 2017; Waller et al 2017; Amico and Goni 2018; Graff et al 2022; Graff et al 2022), we perform exploratory analyses testing the longitudinal stability of the network model in individual participants.…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…Crucially, we find the network model generalizes out of sample, increasing confidence in the model. In line with other dimensional work in neurodiverse populations (Lake et al 2019; Rohr et al 2020; Xiao et al 2021), we observe the brain correlates identified by the model are complex and distributed across broad swaths of cortical, subcortical, and cerebellar regions. Using connectome-based identification (ID) (Finn et al 2015; Kaufmann et al 2017; Vanderwal et al 2017; Waller et al 2017; Amico and Goni 2018; Graff et al 2022; Graff et al 2022), we perform exploratory analyses testing the longitudinal stability of the network model in individual participants.…”
Section: Introductionsupporting
confidence: 89%
“…Crucially, we find the network model generalizes out of sample, increasing confidence in the model. In line with other dimensional work in neurodiverse populations (Lake et al 2019;Rohr et al 2020;Xiao et al 2021), we observe the brain correlates identified by the model are complex and distributed across broad swaths of cortical, subcortical, and cerebellar regions.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…A second limitation is that we chose a set of a-priori ROIs using the social brain atlas since we are interested in predicting individuals’ social abilities. Future studies could examine a different parcellation, such as whole-brain parcellations (Power et al, 2011; Craddock et al, 2012; Shen et al, 2013), given the success of whole-brain FC predictive models (Shen et al, 2017; Beaty et al, 2018; Lake et al, 2019; Xiao et al, 2021). Alternatively, future studies could use atlases developed specifically for children since the brain parcellation used in the current study was derived from adult studies or conduct hyperalignment for better functional alignment (Haxby et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…ASD is primarily manifested as persistent impairments in social communications (SC) and the presence of restricted, repetitive patterns of behaviors, interests, or activities. Despite heterogeneity in behavioral manifestations across sensory and other domains, impaired SC is a core feature of autism ( Pelphrey et al, 2011 ; Xiao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%